(3fMh SjGSI LfGFjI dehGLgI GdLQGFe GdeYdheGJjI (B/s - (3eMeO LeGd OjGH YHOGdLdjds; (3HTjQ SYO RZdhds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2025)
(3YfhGf GdHMK fMh SjGSI LfGFjI dehGLgI GdLQGFe GdeYdheGJjI, hjgOa gPG GdHMK Edi OQGSI eGgjI GdLQjeI GdeYdheGJjI, hJMdjd GdEWGQ GdbGfhfj dehGLgJgG Ydi GdeSJhjjf GdhWfj hGdOhdj, eY JbOje ebJQMGJ dJYRjR GdSjGSI GdLfGFjI hef Cge GdeMGhQ (B: (3eGgjI GdLQjeI GdeYdheGJjI hjJfGhd GdHMK JYQja GdeYdheGJ hGdeYdheGJjI, hTQM eaghe GdLQjeI GdeYdheGJjI eY JMOjO GdEWGQ GdbGfhfj GdefXe dgG (B. (3GdehGLgI GdhWfjI ddLQGFe GdeYdheGJjI hjJe JMdjd GdehGLgI GdJTQjYjI GdhWfjI, ef NdGd OQGSI GdCMcGe GdehVhYjI hGdELQGFjI GdJj JgOa Edi ecGaMI gPg GdLQGFe GdehGLgI GdOhdjI ddLQGFe GdeYdheGJjI jJfGhd GdHMK GdLghO GdOhdjI aj ehGLgI GdLQGFe GdeYdheGJjI, ef NdGd OQGSI GdCMcGe GdehVhYjI aj GdJTQjYGJ GdOhdjI hCgejI GdJYGhf GdOhdj aj ecGaMI gPg GdLQGFe GdSjGSI GdLfGFjI GdebJQMI hjbOe GdHMK MdhdG dJYRjR ecGaMI GdLQGFe GdeYdheGJjI, ef NdGd YbO GdGJaGbjGJ hGdeYGgOGJ GdOhdjI, hJYRjR GdJYGhf GdbGfhfj hGdJbfj Hjf GdOhd(B. (3hef Cge GdJhUjGJ hJTOjO GdYbhHGJ hJWhjQ GdJTQjYGJ hVQhQI eQGLYI GdJTQjYGJ GdhWfjI dJTOjO GdYbhHGJ Ydi GdLQGFe GdeYdheGJjI, HeG jMbb GdQOY GdYGe hGdNGU(B. (3EUOGQ JTQjYGJ NGUI, hEYOGO Odjd EQTGOj hJWhjQ Odjd EQTGOj fXGej hJbfj jhVM BdjGJ GdJYGed eY GdLQGFe GdeYdheGJjI hJOQjH GdLgGJ GdeNJUI hJhajQ HQGeL JOQjHjI eSJeQI ddLgGJ GdbGFeI Ydi JWHjb GdbGfhf, dVeGf age CaVd ddLhGfH GdJbfjI hGdYedjI dgPg GdLQGFe(B. (3JTLjY GdEHdGZ Yf GdLQGFe GdeYdheGJjI hVY BdjGJ JVef MeGjI GdeHdZjf, hJTLjY GdTQcGJ hGdeDSSGJ Ydi YOe GdJSJQ Ydi GdLQGFe GdeYdheGJjI(B. (3ehGcHI GdJWhQGJ GdJbfjI hJMOjK GdbhGfjf HGSJeQGQ dehGcHI GdeSJLOGJ aj eLGd JcfhdhLjG GdeYdheGJ GdJYGhf GdOhdj hJYRjR GdLghO GdOhdjI YHQ JhbjY GJaGbjGJ eTJQcI, hJhMjO GdCfXeI GdbGfhfjI dVeGf aYGdjI GdJYGhf aj ecGaMI GdLQGFe GdeYdheGJjI(B. (3EfTGA LgGR TQWI Ohdj eJNUUI GdYed Ydi EfTGA hMOI TQWI OhdjI eJNUUI aj GdLQGFe GdeYdheGJjI JYed JMJ ETQGa GdCee GdeJMOI, dQHW GdOhd HTHcI eYdheGJjI eQcRjIs
The purpose of this research is to examine what information crime is, analyse the legal framework for countering it at the national and international levels, and make proposals for strengthening criminal policy. One of the most important areas is, what is information crime. The research deals with the definition of information and information crime, the explanation of the concept of information crime, and the definition of the legal framework governing it. National confrontation of information crimes. National legislative confrontation is analysed by examining substantive and procedural provisions aimed at combating such crimes. The international response to cybercrime examines international efforts to combat cybercrime by examining the substantive provisions of international legislation and the importance of international cooperation in combating such crimes. The proposed criminal policy provides solutions to strengthen the fight against cybercrime, through the conclusion of international conventions and treaties, and the promotion of legal and technical cooperation between states. Among the most important recommendations are the tightening of penalties, the development of legislation and the need to review national legislation to increase penalties for information crimes, in order to achieve public and private deterrence. Promulgation of special legislation, preparation of a guide and development of a systematic and technical guide showing mechanisms for dealing with information crime. Training the competent authorities and providing ongoing training programmes to law enforcement agencies to ensure a better understanding of the technical and practical aspects of these crimes. Promote informational crime reporting and establish mechanisms to ensure whistleblower protection, and encourage companies and institutions not to cover up informational crime. Keep abreast of technical developments and constantly update laws to keep abreast of developments in the field of information technology. International cooperation and strengthening of international efforts through the signing of joint conventions and the consolidation of legal systems to ensure effective cooperation in the fight against cybercrime. Establishment of a specialized international police service to work towards the establishment of an international police unit specializing in information crime, under the auspices of the United Nations, to link States to a central information network.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj (B2025s
(3HHdjhLQGajG(B: (3UaMGJ (B403-434s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQjeI GdeYdheGJjIs; (3GdJLGQI GdGdcJQhfjIs; (3GdedcjI GdacQjIs; (3GdEKHGJ GdebjOs; (3eHOC GaJQGV bQjfI GdHQGAIs; (3GdJMbjb GdGHJOGFjs; (3JcfhdhLjG GdeYdheGJs; (3HQhJhchd SJQGSHhQZs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs